2018
DOI: 10.18705/2311-4495-2017-4-6-22-33
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis of Brain Cells in Epileptic Focus at Phapmacresistant Temporal Lobe Epilepsy

Abstract: Российский научно-исследовательский нейрохирургический институт имени профессора А. Л. Поленова, филиал Федерального государственного бюджетного учреждения «Национальный медицинский исследовательский центр им. В.А. Алмазова» Минздрава России, Санкт-Петербург, Россия 2 Федеральное государственное бюджетное учреждение науки «Институт эволюционной физиологии и биохимии им. И.М. Сеченова» Российской академии наук,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…In fact, astrocyte dysfunction has been proposed as a basis for epilepsy, as both animal models and human samples suggest that astrocytes play roles in hyperarousal, neurotoxicity, seizure spread, and other neurogenic functions [15,16]. Furthermore, oligodendrocytes play an important role in epileptogenesis and the development of degenerative processes in DRE [17]. This recognition has led the European Commission of the International League Against Epilepsy (ILAE) to identify glial and inflammatory mechanisms in seizure development and epileptogenesis as a top research priorities, while calling for the identification of glial targets for the development of more specific antiepileptic drugs [18].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, astrocyte dysfunction has been proposed as a basis for epilepsy, as both animal models and human samples suggest that astrocytes play roles in hyperarousal, neurotoxicity, seizure spread, and other neurogenic functions [15,16]. Furthermore, oligodendrocytes play an important role in epileptogenesis and the development of degenerative processes in DRE [17]. This recognition has led the European Commission of the International League Against Epilepsy (ILAE) to identify glial and inflammatory mechanisms in seizure development and epileptogenesis as a top research priorities, while calling for the identification of glial targets for the development of more specific antiepileptic drugs [18].…”
Section: Introductionmentioning
confidence: 99%
“…Astrocyte apoptosis is assumed to activate during and after a convulsive attack and may contribute to neuronal death and epileptogenesis [63]. Our studies have demonstrated that apoptosis can be observed mainly in oligodendrocytes, single astrocytes, and a small part of neurons only (Figure 8) [40,64,65].…”
Section: Glioneuronal Apoptosismentioning
confidence: 76%
“…We have previously shown the presence of apoptosis and neuroinflammation in the temporal lobe of DRE patients [ 9 , 10 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis, oxidative stress, the loss of inhibitory or excitatory neurons, and inflammation play a key role in epilepsy progression [ 7 , 8 , 9 ]. We suggest that since the neuronal and glial components are closely related, it is necessary to study the functioning of both neurons and glia in epilepsy [ 10 ]. Reactive gliosis and inflammation accompanying neuronal damage contribute to the emergence of hyperexcitability focus [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation